A profile of social, separation and generalized anxiety disorders in an Australian nationally representative sample of children and adolescents: Prevalence, comorbidity and correlates. (May 2018) - Spence, Susan H; Zubrick, Stephen R; Lawrence, David
Objective: To examine (1) the 12-month prevalence of social anxiety disorder (SOC), separation anxiety disorder (SEP) and generalized anxiety disorder (GAD) in a large, nationally representative sample of Australian youth; (2) patterns of comorbidity between these disorders; (3) demographic and socio-environmental correlates and (4) the psychosocial impact and service use associated with each condition. Method: Data are from the 2013/2014 Australian national, face-to-face household Young Minds Matter survey of mental health and wellbeing. Informants were parents or carers reporting on 6310, 4- to 17-year-olds (55% of eligible households). The presence of each of the three anxiety disorders was determined based on the Diagnostic Interview Schedule for Children–Version IV. Results: In the past 12 months, 6.6% of youth had experienced at least one of SOC, SEP or GAD, with rates of 2.3% for SOC, 4.3% for SEP and 2.3% for GAD. Rates did not differ by gender but were significantly higher for SOC and GAD and lower for SEP in 12- to 17-year-olds than 4- to 11-year-olds. Comorbidity between these disorders was high, although lower for SEP. Having SOC, SEP or GAD was associated with not living with both biological parents, having a parent with a mental health problem, elevated negative family events, low carer employment and peer victimization. The association with family risk factors was greater for SEP than for SOC and GAD. Although the majority of anxious youth had received professional help, this was less likely in the younger cohort. Conclusion: Social, separation and generalized anxiety disorders in young people are relatively common and impairing, with a high level of comorbidity. There are both commonalities and differences in socio-environmental correlates. The majority of anxious youth received some form of professional assistance, although the rate was lower among children compared to adolescents.